Impacts of Hypoglycemia in At-Risk Infants on Admissions to Level-3 Neonatal Units in a Tertiary-Care Hospital - Alasaad H; Beyyumi E; Zoubeidi T; Khan N; Abu-Sa'da O; Khassawneh M; Souid AK (Dove Medical Press, 2021)
Hala Alasaad,1 Ela Beyyumi,1 Taoufik Zoubeidi,2 Nusrat Khan,1 Omar Abu-Sa'da,1 Mohammad Khassawneh,1 Abdul-Kader Souid3 1Department of Pediatrics, Tawam Hospital, Al Ain, Abu Dhabi, United Arab Emirates; 2Department of Statistics, College of Business and Economics, UAE University, Al Ain, Abu Dhabi, United Arab Emirates; 3Department of Pediatrics, College of Medicine and Health Sciences, UAE University, Al Ain, Abu Dhabi, United Arab EmiratesCorrespondence: Hala AlasaadDepartment of Pediatrics, Tawam Hospital, Al Ain, Abu Dhabi, United Arab EmiratesTel +971 52-6784481Email hasaad@seha.aeIntroduction: Hypoglycemia is frequent in level-1 postnatal units (PNU), which can result in many transfers to the level-3 neonatal unit (NNU).Objectives: This study reports on hypoglycemia (capillary blood glucose < 2.5 mmol/L in the first 24 h) in at-risk infants. Its main objective was to evaluate the impact of hypoglycemia in level-1 PNU on level-3 NNU admissions.Methods: The study was retrospective, conducted between January 01, 2018 and December 31, 2018. Inclusion criteria were infants in the PNU who were: 1) late-preterm (35≤ weeks' gestation < 37), 2) infants-of-diabetic mothers (IDM), and/or 3) low (2.0- 2.5 kg) or high (> 4.0 kg) birthweight.Results: Of the 3192 deliveries, 983 (31%) were eligible for study enrollment; 77% were IDM and 19% late-preterm. A total of 192 (19.5%) newborns had hypoglycemia in the first 4 h and 42 (4.3%) within 4- 24 h. Twenty-two (2.2%) newborns were transferred to NNU, 17 in first 4 h and five within 4- 24 h. Overall, independent predictors of NNU transfer were late-preterm, cesarean delivery, and glucose measurement < 1.5 h (P ≤ 0.019). Independent predictors of hypoglycemia in the first 4 h were late-preterm, cesarean delivery, glucose measurement before feeding, and glucose measurement < 1.5 h (P ≤ 0.045). The independent predictor of hypoglycemia within 4- 24 h was cesarean delivery (P = 0.017). Ten neonates had blood glucose ≤ 1.0 mmol/L; they all required NNU transfer for intravenous glucose.Conclusion: This study shows frequent low glucose readings in these infants (overall prevalence, 23.8%) and confirms the need for clinical observation and regular monitoring. It is prudent to initiate and maintain proper feeding and to adhere to evidence-based guidelines.Keywords: late preterm, cesarean delivery, IDM, neonatal units, newborn feeding